Analysis on the differences between EOP 08C04 and EOP 14C04 related to the Earth rotation characteristics. Issue 1 (2nd January 2022) - Sun, Zhangzhen; Xu, Tianhe; Zhou, Shi'e; Jiang, Nan; Jiang, Chunhua; Yang, Yuguo
ABSTRACT: February 1, 2017, EOP 14C04 aligned to the ITRF2014 was adopted by IERS. To assess the improvement of EOP 14C04, the differences between EOP 14C04 and EOP 08C04 are firstly analyzed. Then, the causes of the differences between the two solutions are examined. Finally, the differences are further assessed for their prediction performance using the LS+AR model. The results demonstrate that (1) there is a trend in the difference between the two solutions; (2) the cause of the above-mentioned difference should be attributed to the different reference frames; (3) the new EOP 14C04 shows better performance for high-frequency signals.